(untitled) (International Journal of Studies in Nursing, 2022)
Objective: To apply nurse-led evidence-based nursing to newly diagnosed patients with type 2 diabetes, and to analyze its effect. Methods: Convenience sampling method was adopted, and 42 patients with initial diagnosis of T2DM who were admitted to the endocrinology department of a tertiary hospital in Chifeng City from September 2021 to February 2022 were included in the study. Grouping was done by random number table method, and finally 21 cases were included in each of the experimental group and the control group. The patients in the control group received routine nursing in the endocrinology department, and the patients in the experimental group received evidence-based nursing led by nurses on this basis. The glucose metabolism indexes and self-management behaviors of the two groups of patients were analyzed. Results: After routine nursing and nurse-led evidence-based nursing for newly diagnosed patients with type 2 diabetes, the blood sugar control of the experimental group was significantly better than that of the control group, and the difference was statistically significant (P<0.05). The behavior was better than that of the control group, and the difference was statistically significant (P<0.05). The nursing satisfaction of the patients in the experimental group was higher than that of the control group, and the difference was statistically significant (P<0.05). Conclusion: In view of the particularity of the newly diagnosed type 2 diabetes patients, in the process of nursing them, the nurse-led evidence-based nursing can effectively control the blood sugar level and improve the patients’ self-esteem based on summarizing the best evidence. Management ability and nursing satisfaction are worthy of promotion and application in clinical practice.